2009
DOI: 10.1266/ggs.84.171
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interaction between WRNIP1 and RAD18

Abstract: WRN interacting protein 1 (WRNIP1) was originally identified as a protein that interacts with the Werner syndrome responsible gene product (WRN). WRNIP1 is a highly conserved protein from E. coli to humans. Genetic studies in budding yeast suggested that the yeast orthlog of WRNIP1, Mgs1, may function in a DNA damage tolerance pathway that is similar to, but distinct from, the templateswitch damage avoidance pathway involving Rad6, Rad18, Rad5, Mms2, and Ubc13. Here we report that human WRNIP1 binds in an ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 34 publications
2
50
1
1
Order By: Relevance
“…The fact that WRNIP1 is associated with these HR proteins, even under unperturbed conditions, raises the possibility that they may exist in a single complex ready to safeguard the integrity of the forks whenever they arrested. Previous studies have shown that WRNIP1 binds to forked DNA, which resembles stalled forks (Yoshimura et al, 2009). Our CldU-IP experiments reveal the association of WRNIP1 with replication forks upon replication stress, suggesting that WRNIP1 could be actually recruited to perturbed forks in vivo, also confirming recent observations from iPOND approaches (Dungrawala & Cortez, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The fact that WRNIP1 is associated with these HR proteins, even under unperturbed conditions, raises the possibility that they may exist in a single complex ready to safeguard the integrity of the forks whenever they arrested. Previous studies have shown that WRNIP1 binds to forked DNA, which resembles stalled forks (Yoshimura et al, 2009). Our CldU-IP experiments reveal the association of WRNIP1 with replication forks upon replication stress, suggesting that WRNIP1 could be actually recruited to perturbed forks in vivo, also confirming recent observations from iPOND approaches (Dungrawala & Cortez, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…7 Moreover, additional in vitro studies revealed that WRNIP1 binds in an ATP-dependent manner to forked DNA that mimics stalled forks. 8 Taken together, these findings strongly support the hypothesis of a specific role of WRNIP1 in the management of perturbed replication forks.…”
supporting
confidence: 71%
“…Binding of WRN to Template-Primer DNA WRNIP1 and WRN bind to a variety of DNA substrates in vitro 22,23) , however, in vivo substrates for these proteins are not known. Since WRNIP1 and WRN are reported to stimulate the DNA synthesizing activity of Pold in vitro, 15,17) substrates used to assay DNA polymerase activity of Pold, which mimic the structure of a primer annealed on a template DNA, were employed to examine the biochemical relationships between WRNIP1 and WRN.…”
Section: Resultsmentioning
confidence: 99%
“…22) Furthermore, WRNIP1 was recruited to DNA bound by RAD18 via protein-protein interactions and displaces RAD18 from the DNA. 22) In this context, it seems likely that WRNIP1 is recruited to the RAD18-DNA complex and displaces RAD18, followed by WRNIP1-induced recruitment of Pold and WRN to the DNA originally recognized by RAD6-RAD18. Next, WRN may displace WRNIP1 and DNA helicase activity of WRN may enhance DNA polymerase activity of Pold in the elongation step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation